Modified constraint-induced movement therapy during hospitalization in children with perinatal brachial plexus palsy: A randomized controlled trial - KARADAĞ SAYGI, NAİME EVRİM (HANLEY & BELFUS-ELSEVIER INC, 2020)
Study Design: Prospective single-blind, randomized controlled study. Introduction: Children with perinatal brachial plexus palsy (PBPP) have motion limitations in the affected upper extremity. Modified constraint-induced movement therapy (mCIMT) is one of the treatment options used for the improvement of the function of the affected limb. Purpose of the Study: The purpose of this study was to compare the effect of mCIMT and conventional therapy in improving active range of motion (ROM) and functional use of the affected upper extremity in children with PBPP with injuries to upper and middle trunks in the hospital environment. Materials: 26 patients received conventional rehabilitation program (control group) and 13 patients participated in a mCIMT program (study group). Children had a mean age 56.3 months (range 4-10 years). The mCIMT included 1 hour therapy sessions emphasizing the affected arm use for 14 consecutive days during hospitalization. Their normal arm was also constrained for 6 hour per day. All the patients were assessed at the baseline, one day, one month, and three months after completion of therapy using active ROM, active movement scale, hand dynamometer, box and blocks test. Results: The mCIMT group improved more than the control group in shoulder internal rotation, forearm supination, elbow flexion active ROMs, hand grip strength, and in upper extremity function. Conclusion: mCIMT has a potential to promote functional gains for children with PBPP; this approach should be widely applied within routine clinical practice. (C) 2020 Hanley & Belfus, an imprint of Elsevier Inc. All rights reserved.
Keywords: Constraint-induced movement therapy; Upper extremity function; Perinatal brachial plexus palsy; HEMIPLEGIC CEREBRAL-PALSY; TRANSCRANIAL MAGNETIC STIMULATION; UPPER-EXTREMITY; UPPER-LIMB; YOUNG-CHILDREN; FOLLOW-UP; INTERVENTION; INJURY; HEMIPARESIS; EFFICACY